The Effectiveness of Using E-Learning Students The University of Lancang Kuning During Covid-19 Using COBIT 5.0 - Nurliana Nasution; Zamzami Zamzami; Fajrizal Fajrizal; Roki Hardianto; Nurul Aien Binti Abd Aziz (AL-ISHLAH: Jurnal Pendidikan, 2022)
During the Covid-19 pandemic, the spread was very wide, including in Indonesia. This affects the student learning system which changes drastically from face-to-face learning to learning at home. The learning solution implemented is online, including for Lancang Kuning University students. The face-to-face learning system applied by Lancang Kuning University changed during the Covid-19 period into distance learning (online) using E-Learning amid the limitations of the existing infrastructure. After implementing the E-Learning system for Lancang Kuning University student lectures, it is necessary to audit academic governance. This audit was conducted to determine the extent to which the implementation of existing information technology was by the academic needs of the Lancang Kuning University community. Evaluation of E-Learning using COBIT 5.0. 4 domains become standards in the COBIT 5.0 assessment, namely Website Content Feasibility Standards, Website Language Feasibility Standards, Website Presentation Feasibility Standards, and Website Component Aspects. In general, the acquisition of the E-Learning index value at Lancang Kuning University has 4 domains, namely Standard indicating good results by showing the total index value is above 3.85. This means that the level of maturity of the Lancang Kuning University student learning system during the Covid 19 period, using E-Learning obtained the predicate "Satisfactory" referring to the predetermined value range method.